Expert System to Diagnose Malaria With Bayes Method - Hutapea, Mei Melan Rut Sartika; Simanjorang, R. Mahdalena (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Malaria is a deadly disease. The disease is caused by a virus that is transmitted through the bite plasmadium Anopheles mosquito tropics. , Indonesia is an area that has a tropical climate so that malaria prevalent in Indonesia. Many public cloud lack of knowledge about the symptoms of malaria because malaria disease symptoms similar to the usual feverish illness. If the disease is not handled seriously can lead to death. From the above explanation makes the excuse needed one expert system that can help people diagnose malaria by looking at symptoms, and later this expert system can explain and diagnose whether a disease malaria or not. In the expert system there are several methods used to menagani a problem. With the solution given institute Bayes Method in helping to diagnose diseases, the expert system that can help people diagnose malaria by looking at symptoms, and later this expert system can explain and diagnose whether a disease malaria or not. Expert System is generally defined as a system that is able to region contribute to solving or handling problems. Expert System is not intended to replace the expert, but to help and support experts. Bayesian methods can diagnose simple encoding and faster calculation. expert system that can help people diagnose malaria by looking at symptoms, and later this expert system can explain and diagnose whether a disease malaria or not. Expert System is generally defined as a system that is able to region contribute to solving or handling problems. Expert System is not intended to replace the expert, but to help and support experts. Bayesian methods can diagnose simple encoding and faster calculation. expert system that can help people diagnose malaria by looking at symptoms, and later this expert system can explain and diagnose whether a disease malaria or not. Expert System is generally defined as a system that is able to region contribute to solving or handling problems. Expert System is not intended to replace the expert, but to help and support experts. Bayesian methods can diagnose simple encoding and faster calculation. Expert System is generally defined as a system that is able to region contribute to solving or handling problems. Expert System is not intended to replace the expert, but to help and support experts. Bayesian methods can diagnose simple encoding and faster calculation. Expert System is generally defined as a system that is able to region contribute to solving or handling problems. Expert System is not intended to replace the expert, but to help and support experts. Bayesian methods can diagnose simple encoding and faster calculation.